2014
DOI: 10.1253/circj.cj-13-0900
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Atrial Fibrillation After Off-Pump Coronary Artery Bypass Grafting Using Preoperative Total Atrial Conduction Time Determined on Tissue Doppler Imaging

Abstract: PA-TDI duration was an independent predictor of POAF following OPCAB. Awareness of risk of POAF may lead to the prevention of POAF, a rapid response to POAF, shortened hospital stay, and improved prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 30 publications
5
30
1
1
Order By: Relevance
“…8 In our previous study in patients undergoing off-pump CABG, a PA-TDI duration >141 ms was found to be a predictor of POAF. 9 In the present study, we found that the occurrence of POAF in patients with a PA-TDI duration <130 ms (6/22 cases (27%)) and the optimal cutoff value of the PA-TDI duration was >147 ms. The difference in the optimal PA-TDI cutoff values in our 2 studies may have be related to the extent of invasive surgical manipulation and the underlying disease (coronary artery disease or AS).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…8 In our previous study in patients undergoing off-pump CABG, a PA-TDI duration >141 ms was found to be a predictor of POAF. 9 In the present study, we found that the occurrence of POAF in patients with a PA-TDI duration <130 ms (6/22 cases (27%)) and the optimal cutoff value of the PA-TDI duration was >147 ms. The difference in the optimal PA-TDI cutoff values in our 2 studies may have be related to the extent of invasive surgical manipulation and the underlying disease (coronary artery disease or AS).…”
Section: Discussionsupporting
confidence: 47%
“…27 The new information from our previous study was that the PA-TDI duration was also an independent predictor of POAF in patients undergoing offpump CABG. 9 The aim of the present study was to determine the optimal cutoff value of PA-DTI duration to predict POAF. de Vos et al showed that in 249 patients with cardiac disease, the PA-TDI study included patients who underwent isolated AVR; however, some patients had mitral valvular disease as well, which may have increased the risk of POAF.…”
Section: Study Limitationsmentioning
confidence: 98%
“…22 It is well known that POAF is influenced by multiple risk factors. 23, 24 The preoperative factors include age, hypertension and diabetes mellitus; the intraoperative factors include operative stress and atrial ischemia; and the postoperative factors include volume overload, increased cardiac afterload, and inflammation. These changes may affect the atrial structural substrate for POAF, and cause atrial extrasystoles and/or autonomic nerve imbalance, triggering electrophysiological disorders including atrial flutter and fibrillation.…”
Section: Tashiro N Et Almentioning
confidence: 99%
“…Three recent echocardiographic studies assessed the predictive value of pulsed-wave (PW)- DMI in patients prior to cardiac surgery [23-25]. Here, the time interval between onset of P-wave and peak of A’-wave derived from PW-DMI of the left lateral atrial wall was measured.…”
Section: Discussionmentioning
confidence: 99%